Pengaruh Lingkungan Kerja dan Stres Kerja terhadap Kinerja Aparatur Sipil Negara di Bagian Umum Sekretariat Daerah Kota Malang - Andi Yudi Setiawan; Andi Nu Graha; Sri Wilujeng (Jurnal Riset Mahasiswa Manajemen, 2019)
The purpose of this study was to determine the effect of the work environment and work stress on the performance of the state civil apparatus in the general section of the malang city secretariat, to determine the influence of the work environment on the performance of the state civil apparatus in the general section of the malang city regional secretariat, to determine the effect of work stress on the government employee the state in the general section of the Malang City secretariat. The variables used are the work environment and work stress as an independent variable and the performance of the state civil service as the dependent variable. The sample used was all state civil servants in the general section of the Malang City secretariat which amounted to 60 respondents, sampling using saturated sampling techniques. The data collection method used was a questionnaire (questionnaire). The analysis used includes the validity test, reliability test, classic assumption test, multiple linear regression analysis test, and hypothesis testing. The results of this study indicate that the work environment and work stress variables affect the government employee in the general part of the Malang City secretariat, the work environment influences the government employee in the general part of the Malang city secretariat, and work stress affects the government employee in the general section of the Malang City Secretariat.